2020
DOI: 10.3390/land9050150
|View full text |Cite
|
Sign up to set email alerts
|

From City- to Site-Dimension: Assessing the Urban Ecosystem Services of Different Types of Green Infrastructure

Abstract: Cities have a wide variety of green infrastructure types, such as parks and gardens. These structures can provide important ecosystem services (ES) with a major impact on human well-being. With respect to urban planning, special consideration must be given to such green infrastructure types when implementing measures to maintain and enhance the quality of life. Therefore, generating knowledge on the urban ES of differently scaled green infrastructure types is important. This systematic literature review provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…According to the Attention Restoration Theory (ART) developed by Kaplan, mental restoration can be defined as the renewal of "adaptive resources" depleted in ongoing efforts to meet the demands of everyday life [4]. There is evidence suggesting that the natural environment is perceived to have better restorative properties than artificial urban settings [5][6][7][8]. Sounds are an essential part of the natural environment, and emerging research has demonstrated that natural sounds might have potential benefits for health and well-being [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Attention Restoration Theory (ART) developed by Kaplan, mental restoration can be defined as the renewal of "adaptive resources" depleted in ongoing efforts to meet the demands of everyday life [4]. There is evidence suggesting that the natural environment is perceived to have better restorative properties than artificial urban settings [5][6][7][8]. Sounds are an essential part of the natural environment, and emerging research has demonstrated that natural sounds might have potential benefits for health and well-being [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A further step could also be to consider incorporating economic and non-economic values of urban ecosystem services. Brzoska and Spāge (2020), note that exploiting the multiple benefits of urban ecosystems requires generating knowledge, expertise, and information on the multiple functions and services of urban greenspaces on different spatial scales. But, as they note, this is even more so the case when it comes to the small spatial scales where planned measures are realized.…”
Section: Subsidiarity and The City Levelmentioning
confidence: 99%
“…However, advancing from theory to implementation requires not only further advances in the science of ecosystem services, but also recognition at all levels of government of their multiple monetary and non-monetary benefits to society and human well-being (Daily and Matson, 2008;Young, 2013). It is with the latter area that this study is concerned, as scholarly work has indicated that little knowledge exists about the extent to which ecosystem-based approaches to environmental protection have been integrated or mainstreamed into national, but especially municipal planning (Pasquini and Cowling, 2015;Wamsler and Pauleit, 2015;Brzoska and Spāge, 2020). This is particularly the case with regards to sub-Saharan Africa, as the bulk of research focuses on European urban centers, followed by Asia and the Americas (Brzoska and Spāge, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mcfarland et al (2019) discussed the stormwater management of green infrastructure and reviewed the relevant literature to provide storm-water management guidelines for different types of green infrastructures (McFarland et al, 2019). Brzoska and Sp a ge (2020) investigated the evaluation of ecosystem services in green infrastructure, and analyzed 76 papers published from 2000 to 2019 in WOS and Scopus to obtain the main types and generalized methods of the evaluation of ecosystem services in green infrastructure (Brzoska & Sp a ge, 2020). In addition, studies have analyzed the research hotspots and development trends of green infrastructure.…”
Section: Introductionmentioning
confidence: 99%